การพัฒนาเครื่องทำแกรนูลแบบฟลูอิดไดซ์เบด ระดับเล็ก - กิตติพงษ์ พัฒนทอง (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
Objective of this research is to design and test a small-scale fluidized bed granulator employed for pharmaceutical propose. Investigation on influence of operating variables (fluidizing air velocity, fluidizing air temperature and atomizing air pressure) and type of raw materials (lactose powder and lactose and corn starch powder blended by a mixing ratio 70 to 30 w/w) to size distribution, average particle size, shape and physical properties have been carried out. The granules produced are taken to produce tables by using single punch tableter machine. Physical properties of tables (such as weight variation, hardness, thickness, diameter, friability and disintegration time) have been also investigated. Comparison of the properties of the tables with those of spray dry lactose (Tablettose) tables are then conducted. From experimental results, granules produced at low fluidizing air velocity (0.8 m/s) have larger mean particle size than those obtained when air velocity is higher. Meanwhile fluidizing air temperature has little effect on the mean particle size of the granules. However, atomizing air pressure applied to the spraying nozzle has a significant effect on the mean particle size and the size distribution of the granules. An increase in the atomizing air pressure gives rise to an increase in amount of fine particles then results in the smaller mean particle size. An increase in mean particle size of the granules produced yields increasing aerated bulk density but decrease its angles of repose, compressibility and packed bulk density. From these results, it is found that the flowability index of the granules becomes increased while the floodability index decreases. From scanning electron microscope photograph, it is clear by seen that inside the granules formed, a particle wetted by binder has several contact with other particles. Considered from the granule morphology, it can be implied that the granule is formed by the so-called snow-balling mechanism, so that spherical granules are obtained. In tabletation process, the granules with higher mean particel size results in the less weight variation and friability of tablets produced. Moreover, the tablets produced from lactose and corn starch mixture have shorter disintegration time than those of lactose granules. In conclusion, the tables produced from the granules, which are obtained from the developed granulator have an acceptable qualities compared with those Tablettose using the USP standard.